# Proving the distributive law with natural deduction

I have to prove the following logical equivalence, also known as one of the two distributive laws:

$$P \vee (Q \wedge R) \equiv (P \vee Q) \wedge (P \vee R)$$

I have solved the first part, $P \lor (Q \land R) \to (P \lor Q) \land (P \lor R)$, like so: But now that I'm trying to solve the next part, $(P \lor Q) \land (P \lor R) \rightarrow P \lor (Q \land R)$, I keep getting stuck somewhere with a disjunction elimination where I'm trying to prove something like $P$ with only $Q$ and $(P ∨ Q) ∧ (P ∨ R)$.

So how can I prove $(P \lor Q) \land (P \lor R) \rightarrow P \lor (Q \land R)$ using a proof tree, like shown above? Thanks!

• Unpack the premise with $\land$-elim; then two "nested" $\lor$-elim. Three cases : 1) $P$ : done. 2) $Q$ then $P$ : done. 3) $Q$ then $R$ : done. – Mauro ALLEGRANZA Sep 7 '18 at 20:11
• @MauroALLEGRANZA Thank you for commenting, but I'm not sure I understand. After I've used implication introduction on the premise ($P∨(Q∧R)$), wouldn't I have to use disjunction elimination before being able to do a conjunction elimination as you suggest? – tobloef Sep 7 '18 at 20:43

Let $A = (P \lor Q) \land (P \lor R)$ and $B = P \lor (Q \land R)$.
The following is a derivation in natural deduction of $B$ from $A$.
$$\dfrac{\dfrac{A}{P \lor Q}\land_{e_1} \quad \dfrac{[P]^*}{B}\lor_{i_1} \quad \dfrac{\dfrac{A}{P \lor R}\land_{e_2} \quad \dfrac{[P]^{**}}{B}\lor_{i_1} \quad \dfrac{\dfrac{[Q]^* \quad [R]^{**}}{Q \land R}\land_i}{B}\lor_{i_2}}{B}\lor_e^{**}}{B} \lor_e^*$$
Note that the derivation above is based on two nested applications of the rule $\lor_e$.
From the derivation above you obtain the derivation of $A \to B$ (without assumptions) by adding a $\to_i$ rule as last rule, discharging the two occurrences of $A$.